Convenient Chemoenzymatic Route to Optically Active β‐Aryl‐δ‐iodo‐γ‐lactones and β‐Aryl‐γ‐iodo‐δ‐lactones with the Defined Configurations of Stereogenic Centers. Issue 3 (9th December 2014) - Gładkowski, Witold; Skrobiszewski, Andrzej; Mazur, Marcelina; Siepka, Monika; Białońska, Agata
Abstract: Two δ‐iodo‐γ‐lactones and two γ‐iodo‐δ‐lactones substituted at the β‐position with phenyl or 4‐methylphenyl ring have been synthesized in both enantiomeric forms. The starting materials were enantiomerically enriched allyl alcohols with an ( E )‐4‐phenylbut‐3‐en‐2‐ol system ( ee in the range 88–99 %), which were obtained by lipase‐catalyzed transesterification. Alcohols were subjected to orthoacetate modification of the Claisen rearrangement. The high stereoselectivity of this reaction led to retention of ( E )‐configuration of the double bond and complete transfer of chirality from the allyl alcohol to the benzylic position C‐3. As a result, chiral γ, δ‐unsaturated esters with retained configuration of the stereogenic center were produced. Their hydrolysis and iodolactonization afforded new enantiomers of iodolactones with high or excellent ee (97–99 %). Their configuration at C‐4 was a direct result of the configuration at C‐3 of the acid subjected to iodolactonization, whereas stereocenters at C‐5 and C‐6 were formed as a consequence of the reaction mechanism. For most of the synthesized isomers, the predicted configurations were established by X‐ray analysis. The presented chemoenzymatic pathway represents a useful strategy that can be applied in the asymmetric synthesis of variety of lactones from 4‐arylbut‐3‐en‐2‐ols. Abstract : Iodolactones substituted at the β‐position with a phenyl or 4‐methylphenyl ring have been synthesized in both enantiomeric forms. Starting materials were allyl alcohols, which were resolved by a lipase‐catalyzed transesterification process. The configurations of the iodolactones were either established by X‐ray analysis or predicted on the basis of the iodolactonization mechanism.